Distribution Pattern and Controlling Factors of Reef–Shoal Reservoirs on Both Sides of the Intra-Platform Depression in the Changxing Formation, Wolonghe-Yangduxi Area, Sichuan Basin - Yuhang Bi; Zhonggui Hu; Saijun Wu; Jiuzhen Hu; Weijie Tong; Min Yao (Applied Sciences)
The development pattern of the high-quality reservoir in the Changxing Formation in the Wolonghe-Yangduxi area of southeastern Sichuan is complex. To clarify its evolution, genetic mechanisms, and distribution patterns, this study integrates data from profiles, cores, thin sections, and well logs. It reveals the distribution mechanisms of the bio-reef and shoal reservoirs in the Changxing Formation and discusses the controlling effects of tectonic, sedimentary, and diagenetic processes on reservoir development. The results show the following: (1) The Changxing Formation mainly develops open platform facies, platform margin facies, and slope-basin facies, which can be further subdivided into subfacies of platforms, intra-platform depressions, intra-platform depressions marginal reefs, and intra-platform depressions marginal shoals. The intra-platform margin reefs and the reefs at the edge of the platforms are favorable microfacies for reservoir development. (2) The high-quality reservoirs of the Changxing Formation are dominated by medium-thick-layered biogenic reef limestone and bioclastic limestone, with secondary porosity as the main reservoir space. (3) Sedimentary conditions, sea level fluctuations, and diagenesis are crucial factors for reservoir development. Paleogeomorphological conditions provide the foundation for reservoir development, while sea level fluctuations control the internal structure of the reef–shoal and the cyclical variations in the reservoir.